Feeding Preferences, Growth Patterns and Reproductive Characteristics of Fall Armyworm (Spodoptera frugiperda) Indicate the Potential of Ficus Tree as New Host Plant - Changqi Chen; Yan Wang; Yana Zhou; Zhu Liu; Zongbo Li; Yuan Zhang (Agriculture)
The fall armyworm, Spodoptera frugiperda, is a serious invasive pest of the family Noctuidae (Lepidoptera) that poses a significant threat to global crop production, with poaceae crops being particularly affected. Previous studies have indicated that, as a voracious insect, the fall armyworm possesses the potential for food source diversification. However, to date, limited research has been conducted on whether plants other than maize (Zea mays L.) and rice (Oryza sativa L.) can serve as potential food resources for the pest. In Yunnan Province, China, the distribution ranges of the fall armyworm and Ficus plants show a significant degree of overlap. Ficus species, including the widely distributed Ficus microcarpa L. f., commonly grow within or near cornfields. Our previous field studies have documented instances of fall armyworms in cornfields exhibiting feeding behavior on F. microcarpa. In this study, maize and F. microcarpa were selected as food resources for fall armyworms to compare larval feeding preferences, development time, survival rate, and reproductive capacity. The results demonstrated that when both maize and F. microcarpa were available simultaneously, fall armyworm larvae consumed both plant species. Further analysis revealed that larvae feeding on F. microcarpa exhibited a significantly longer developmental period from the third stage to pupation (14.08 ± 0.44 d) compared to those feeding on maize (9.21 ± 0.14 d). Moreover, the pupae size, pupae weight, and egg count were reduced by approximately 10%, 30%, and 30%, respectively, in larvae that fed on F. microcarpa. Despite these physiological challenges, our research findings indicated that, despite F. microcarpa not being the primary food source for fall armyworms under natural conditions, fall armyworms feeding on F. microcarpa were still capable of completing the life cycle from the third instar to the second generation when relying solely on F. microcarpa. Therefore, it is crucial to strengthen the observation and monitoring of fall armyworm populations feeding on F. microcarpa and implement targeted control strategies according to specific circumstances, thereby preventing F. microcarpa from acting as a potential host.